Implementasi Pembelajaran Inklusif dengan Menggunakan Media Gambar bagi Anak ADHD di SDN Kemuning Tarik Sidoarjo - Amelia Putri, Arnetta; Nova Estu Harsiwi (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2025)
Inclusive education is an education system that is friendly to all individuals without distinguishing the diversity of their characteristics. This system provides educational services that allow children with special needs to learn with their peers in the public school closest to where they live. This study aims to examine the "Implementation of Inclusive Learning for Children with Attention Deficit Hyperactivity Disorder (ADHD) at SDN Kemuning Tarik Sidoarjo", especially in inclusive classes. This study applies a qualitative approach with data collection methods through observation, in-depth interviews, and documentation. The research findings reveal that the implementation of inclusive learning has attempted to answer the needs of children with ADHD, although there are still a number of obstacles such as minimal training for teachers and limited supporting facilities. Strategies that have been successfully implemented include the use of an individual approach, positive reinforcement, and curriculum adaptation. Increased collaboration between parties and policy support from schools are needed for the sustainability of inclusive and effective learning.